IMPLEMENTING THE SQ3R TECHNIQUE THROUGH PREZI MEDIA TO TEACH READING COMPREHENSION OF NARRATIVE TEXT (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2026)
This study investigated the effect of implementing the SQ3R (Survey, Question, Read, Recite, Review) technique assisted by Prezi media on students’ reading comprehension of narrative texts. The research was conducted in Class XB of MAS Darussalam Mempawah during the 2025/2026 academic year with a sample of 29 students, who were selected through cluster random sampling. The study used a pre experimental design with a one-group pre-test and post-test. The instrument was a set of 30 multiple-choice items, which were tested for validity, reliability, difficulty level, and discriminative power. Data were analyzed using descriptive statistics, a normality test, and hypothesis testing through the Paired Sample t-test. The results indicated a significant improvement in students’ reading comprehension. The mean pre-test score was 54.97, which increased to 81.66 in the post-test, showing a difference of 26.69 points. The normality test confirmed that the data were normally distributed, and the paired sample t-test yielded a significance value of 0.000 (p < 0.05), demonstrating a significant difference between the pre-test and post-test scores. Therefore, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. These findings demonstrated that the SQ3R technique, when supported by Prezi as a visual aid, was effective in enhancing students’ comprehension of narrative texts.